Kepuasan Pengguna Fitur Medis ePuskesmas dengan Model EUCS dan DeLone & McLean di Sumedang - Agun Guntara; Irfan Fadil; Siti Nurhayati (FKOM UNIKU, 2024)
An ePuskesmas is a health information system developed through the collaboration of the Sumedang District Health Office and PT Infokes Indonesia. It offers various features to aid health workers at Puskesmas, notably the medical feature for managing patient data during polyclinic examinations. However, this feature faces issues such as synchronization difficulties with Pcare, slow system responses due to high user traffic, and frequent errors. This study aims to assess user satisfaction with the medical features of ePuskesmas using the End User Computing Satisfaction (EUCS) model and the DeLone and McLean Model. The study involves 93 respondents, including nurses, midwives, and doctors from Sumedang Regency Health Center, selected through purposive sampling. Data analysis is performed using SmartPLS 3.2.9 with PLS-SEM. The results indicate overall user satisfaction with the medical features of ePuskesmas. Out of 8 hypotheses, 3 are accepted, and 5 are rejected. Key factors influencing user satisfaction include Accuracy, Ease of Use, and Information Quality. This research is important to find out whether the system developed by related parties is in accordance or not with the end user